Management of Recurrent Keratitis as a Complication of Androctonus crassicauda Black Scorpion Sting: A Case Report - Alqudah A; Bani Yassin AR; Yaseen S; El Taani L (International Medical Case Reports Journal)
Asem Alqudah, Abdel Rahman Bani Yassin, Said Yaseen, Leen El Taani Division of Ophthalmology, Department of Special Surgery, Faculty of Medicine, Jordan University of Science and Technology (JUST), Irbid, JordanCorrespondence: Asem Alqudah, Division of Ophthalmology, Department of Special Surgery, Faculty of Medicine, Jordan University of Science and Technology, Irbid, Jordan, Tel +962795458496, Email asemq981@yahoo.comAbstract: Scorpions are a group of arthropods known to be highly toxic to humans. We report the case of a previously healthy 61-year-old male who sustained a sting from an Androctonus crassicauda scorpion to his right eye. The patient was admitted to the intensive care unit (ICU) in a comatose state immediately after the sting. A few days later, he suffered from tearing right-eye pain and loss of vision, which persisted despite initial treatment. The patient was subsequently diagnosed with keratitis and admitted to King Abdullah University Hospital (KAUH). He was prescribed various antibiotics, which initially improved his condition. However, the patient experienced subsequent deterioration and recurrent episodes of keratitis. The patient’s visual acuity improved after treatment with a combination of antifungal and antibiotic medications, suggesting a polymicrobial infection. Despite the improvement in his condition, the sting left a central corneal scar, necessitating corneal transplant surgery as a definitive treatment. To the best of our knowledge, this scenario has not been previously documented.Keywords: scorpion bite, keratitis, corneal transplantation, corneal ulceration, ocular, Androctonus crassicauda